SPEECH ACTS OF THE BRONTE SISTERS’ CHARACTERS - Suryanovika, Citra; Manda Negara, Irma (HUMANIKA, 2018)
The study was under descriptive qualitative research to identify the most dominant speech act of the Bronte Sisters’ characters. The researchers collected 3,322 utterances from six characters of Charlotte Bronte’s Jane Eyre (Jane Eyre and Edward Rochester), Emily Bronte’s Wuthering Heights (Heathcliff and Catherine Earnshaw), and Anne Bronte’s The Tenant of Wildfell Hall (Gilbert Markham and Helen Graham). MAXQDA 2018 supported the data analysis procedure; thus, coding was used in identifying speech acts. After coding implemented, the researchers analyzed the coding by using qualitative and quantitave compare groups, as well as document comparison chart in MAXQDA 2018 to check the most dominant use of speech acts in all characters. The study found that directive speech act is the most dominant speech act found in the Bronte sisters’ characters, while the declarative speech act is the least speech act. Speech acts of the Bronte sisters’ characters was expressed in declarative, interrogative and imperative forms.  Besides, speech acts in these novels highlight the use of address term, epithet, expression (verb, adjective, modal verbs), exclamation, conditional clauses, hedges and affirmative answer.